2000
DOI: 10.1046/j.1365-2818.2000.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic cleavage in living zoosporangia of Allomyces macrogynus

Abstract: We have used the vital fluorescent dye, FM4-64, as a marker of membrane development during zoospore formation in living zoosporangia of Allomyces macrogynus. Membrane development was visualized and documented using standard epifluorescence and laser scanning confocal microscopy. Video-enhanced light microscopy and transmission electron microscopy, using cryopreparation methods, were also employed in this study. In the first 10-12 min after the induction of zoospore formation, only the plasma membrane labelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…1b), there is no indication that the long lag-phase is caused by nuclear divisions. However, preliminary electron-microscopical studies of mature sporangia indicate that the nuclei are not separated by plasma membranes, consistent with findings in other oomycetes such as Phytophthora cinnamomi (Hyde and Hardham 1993) and Allomyces macrogynus (Fisher et al 2000). The sporangium therefore represents a syncytium, and during the period prior to zoospore release the individual zoospores have to be separated from each other.…”
Section: Discussionsupporting
confidence: 80%
“…1b), there is no indication that the long lag-phase is caused by nuclear divisions. However, preliminary electron-microscopical studies of mature sporangia indicate that the nuclei are not separated by plasma membranes, consistent with findings in other oomycetes such as Phytophthora cinnamomi (Hyde and Hardham 1993) and Allomyces macrogynus (Fisher et al 2000). The sporangium therefore represents a syncytium, and during the period prior to zoospore release the individual zoospores have to be separated from each other.…”
Section: Discussionsupporting
confidence: 80%
“…In a higher magnification, these membranes responsible for the cleavage of cytoplasm were observed as paired membranes (Fig. 1B) and morphologically equivalent to the cleavage membranes described in the study of the cytoplasmic cleavage of multinucleate zoosporangia of A. macrogynus (Fisher et al, 2000;Lowry et al, 2004). Paired membranes could be easily distinguished from other membranous structures even at low magnification by their thickness, dark staining, smooth surface, and resistance to ice damage.…”
Section: Electron Microscopysupporting
confidence: 71%
“…It has been reported that the fluorescent, lipophilic styryl dye FM4-64 was highly specific in staining the plasma membrane and the cleavage elements during the development of multinucleate zoosporangia of A. macrogynus (Fisher et al, 2000). FM4-64 also stained the plasma membrane and the internal membranes of the binucleate zoosporangia (Fig.…”
Section: Live-cell Confocal Microscopymentioning
confidence: 84%
See 2 more Smart Citations